An MS Excel Add-in for Calculating Darcy Friction Factor - Duman, Selin; Demir, Selami; Demir, Neslihan Manav; Karadeniz, Aykut (BOND UNIV, FAC BUSINESS SCH INFORMATION TECHNOLOGY, 2018)
An MS Excel add-in was prepared for calculating Darcy friction factor. The tool contains a function named FFACTOR and it calculates friction factor under laminar, transient, and turbulent conditions. Under turbulent conditions, the function employs a total of 25 friction factor models and the user can select one of these to calculate Darcy friction factor. Tip texts and pop-up help were also prepared and are available if open-source Excel-DNA Intellisense add-in is also added to MS Excel. The students can benefit from the MS Excel add-in. Also, professors can use it for teaching purposes
Keywords: MS Excel add-in; Darcy friction factor; Colebrook Equation; Friction factor models; EXPLICIT APPROXIMATIONS; COLEBROOKS EQUATION; TURBULENT-FLOW; SMOOTH PIPES; FORMULAS; REGIMES; ROUGH; Education & Educational Research